Efficacy of triclopyr and synthetic auxin herbicide mixtures for common blue violet (Viola sororia) control. (29th August 2020) - Patton, Aaron J.; Weisenberger, Daniel V.; Liu, Wenwen
Abstract: Common blue violet is a widely distributed, perennial broadleaf that is difficult to control in lawns. Two experiments were conducted to evaluate the efficacy of synthetic auxin herbicides and their mixtures or rate for common blue violet control. A herbicide comparison experiment was conducted with treatments including a nontreated check; 2, 4-D dimethylamine; 2, 4-D isooctyl ester (2, 4-D ester); dichlorprop (2, 4-DP) ethylhexyl ester, MCPA dimethylamine; mecoprop dimethylamine; triclopyr butoxyethyl ester; quinclorac; and mixtures of triclopyr + quinclorac; 2, 4-D ester + 2, 4-DP; 2, 4-D ester + triclopyr; 2, 4-D ester + 2, 4-DP + triclopyr. All herbicides were applied at 1.12 kg ae ha −1 except quinclorac (0.84 kg ha −1 ). Additionally, a triclopyr dose-response experiment was conducted using rates of 0, 0.14, 0.28, 0.56, 0.84, and 1.12 kg ha −1 . Epinasty ranged from 80% to 99% at 21 d after application for triclopyr-containing treatments and no more than 28% for all other treatments. Plant mass from harvest and regrowth data from the comparison experiment indicated triclopyr-containing treatments provided the highest common blue violet control. Mixtures containing triclopyr did not differ from triclopyr alone, indicating there was no added effect between herbicide mixtures. The triclopyr dose-response experiment confirmed triclopyr efficacy across data collection types. As triclopyr dose increased, violet epinasty increased and chlorophyll content and dry weight decreased. Triclopyr applied at 0.81 kg ha −1 or greater concentration provided 75% or greater control, as indicated by regrowth data. Many herbicides containing triclopyr are registered for use in turf, but most apply a concentration not greater than 0.56 kg ha −1 triclopyr when applied at the high label rate. Thus, to achieve good (75%) common blue violet control, turf managers should select products that contain triclopyr and apply doses of at least 0.81 kg ha −1 when used according to the label.